PANCHAYATI RAJ AND DEMOCRATIC PARTICIPATION: AN ANALYSIS OF LOCAL SELF-GOVERNMENT IN THE STATE OF UTTAR PRADESH - Trivedi, Sudhanshu; Yadav, Prateek; Rai, Shubham; Asagar, Mirza Shahzan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Panchayati Raj system in India represents one of the most crucial innovations in post-independence political restructuring, aiming to deepen democratic values and foster inclusive development. Formally institutionalized through the 73rd Constitutional Amendment of 1992, Panchayati Raj Institutions (PRIs) were established as mechanisms for decentralizing governance to rural areas. The objective was to enable local populations to take part in decision-making processes directly affecting their lives. In the state of Uttar Pradesh, the effectiveness of PRIs is particularly vital, given the size, diversity, and complex socio-economic conditions of its population. This paper examines the theoretical foundations of Panchayati Raj, the historical evolution of local self-governance, and how democratic participation has been facilitated or hindered by the system in Uttar Pradesh. Focusing on administrative and financial decentralization, the paper delves into the challenges of governance, representation, and participation, highlighting the socio-political dynamics of the region. The study concludes with an exploration of the possible pathways for reinforcing democratic values and improving the functioning of PRIs in the state.